OPEN RESONATOR FOR SUMMATION OF POWERS IN SUB-TERAHERTZ AND TERAHERTZ FREQUENCIES - Kuz’michev, I. K.; Yeryomka, V. D.; Маy, A. V.; Troshchilo, A. S. (Видавничий дім «Академперіодика», 2017)
PACS number: 07.57.-c   Purpose: Study of excitation features for the first higher axialasymmetric type oscillations in an open resonator connected into the waveguide transmission line.Design/methodology/approach: To determine the efficiency of higher oscillation excitation in the resonator by using the highest wave of a rectangular waveguide, the coefficient of the antenna surface utilization is used. The coefficient of reflection from the open resonator is determined by the known method of summation of the partial coefficients of reflection from the resonant system.Findings: The excitation efficiency of the first higher axial asymmetric type TEM10q oscillations in an open resonator connected into the waveguide transmission line, using the TE20 type wave, is considered. The research efforts were made with accounting for the electromagnetic field vector nature. It is shown that for certain sizes of exciting coupler the excitation efficiency of the working excitation is equal to 0.867. Besides, this resonant system has a single frequency response within a wide band of frequencies. Due to this, it can be applied for summation of powers for individual sources of oscillations. Since this resonant system allows separating the matching functions as to the field and coupling, it is possible to provide any prescribed coupling of sources with a resonant volume. For this purpose, one-dimensional diffraction gratings (E-polarization) are used.Conclusions: With the matched excitation of axially asymmetric modes of oscillations the resonant system has an angular and frequency spectrum selection that is of great practical importance for powers summation. By application of one-dimensional diffraction gratings (E-polarization), located in apertures of coupling elements, the active elements can be matched with the resonant volume.Keywords: terahertz frequencies, open resonator, rectangular waveguide, oscillation excitation efficiency, summation of powersManuscript submitted 28.08.2016Radio phys. radio astron. 2017, 22(1): 67-77 REFERENCES1. SIEGEL, PETER H., 2002. Terahertz Technology. IEEE Trans. Microw. Theory Tech. vol. 50, no. 3, pp. 910–928. DOI: https://doi.org/10.1109/22.989974 2. SITNIKOV, A. G., MIKHAILOV, V. M. and TELMINOV, A. E., 2009. Terahertz radiation: application in molecular spectroscopy and sources of molecular radiation. Optika atmosfery i okeana. vol. 22, no. 11, pp. 1092–1098 (in Russian). 3. POPOVIC, Z. and GROSSMAN, E. N., 2011. THz metrology and instrumentation. IEEE Trans. THz Sci. Technol. vol. 1, no. 1, pp. 133–144. DOI: https://doi.org/10.1109/TTHZ.2011.2159553 4. KULIPANOV, G. N., 2010. Generation and application of terahertz radiation: history and perspective. Vestnik Novosibirsk State University. Series: Physics. vol. 5, is. 4, pp. 24–27 (in Russian). 5. SVETLITZA, A., SLAVENKO, M., BLANK, T., BROUK, I., STOLYAROVA, S. and NEMIROVSKY, Y., 2014. THz Measurements and Calibration Based on a Blackbody Source. IEEE Trans. THz Sci. Technol. vol. 4, no. 3, pp. 347–359. DOI: https://doi.org/10.1109/TTHZ.2014.2309003 6. KARUSHKIN, N. F., KASATKIN, L. V. and MALTSEV, S. B., 2006. Experience in Development of High Power IMPATT Diode Sources for MM-Wave Range. In: 16th International Crimean conference on Microwave and telecommunication technology CriMiCo'06 Proceedings. 11-15 Sept. 2006. Sevastopol, Ukraine, vol. 1, pp. 135–137 (in Russian). DOI: https://doi.org/10.1109/CRMICO. 2006.256331 7. ISAEV, V. M., KABANOV, I. N., KOMAROV, V. V. and MESANOV, V. P., 2014. Modern radio-electronic systems of terahertz frequency range. Proceedings of Tomsk State University of Control Systems and Radioelectronics. no. 4 (34), pp. 5–21 (in Russian). 8. BORODKIN, A. I., BULGAKOV, B. M., MATVEEVA, V. A., RODIONOV, A. V., SMORODIN, V. V. and SHESTOPALOV, V. P., 1979. Semiconductor generator of millimeter range with quasi-optical resonator system. Pis'ma Zh. Tekh. Fiz. vol. 5, is. 5, pp. 285–288 (in Russian). 9. OVECHKIN, S. M., REBROV, S. I., SAZONOV, V. P., SINITSYN, V. V. and TAGER, A. S., 1984. Addition of power of Gunn diodes in open microwave resonator. Pis'ma Zh. Tekh. Fiz. vol. 10, is. 6, pp. 367–370 (in Russian). 10. MIZUNO, K., AJIKATA, T., HIEDA, M. and NAKAYAMA, M., 1988. Quasi-optical resonator for millimetre and submillimetre wave solid-state sources. Electron. Lett. vol. 24, no. 13, pp. 791–793. DOI: https://doi.org/10.1049/el:19880538 11. JONGSUCK B., ABURAKAWA Y., KONDO H., TANAKA T. and MIZUNO, K., 1993. Millimeter and submillimeter wave quasi-optical oscillator with Gunn diodes. IEEE Trans. Microw. Theory Tech. vol. 41, no. 10, pp. 1851–1855. DOI: https://doi.org/10.1109/22.247932 12. JUDASCHKE, R., HÖFT M. and SCHÜNEMANN, K., 2005. Quasi-optical 150-GHz power combining oscillator. IEEE Microw. Compon. Lett. vol. 15, no. 5, pp. 300–302. DOI: https://doi.org/10.1109/LMWC.2005.847660 13. DVORNIKOV, A. A. and UTKIN, G. M., 1974. Addition of power of many oscillators. Radiotekhnika i Elektronika. vol. 19, no. 3, pp. 550–559 (in Russian). 14. TYAGI, R. K. and SINGH, D., 1996. Quasi-optical resonator for power combining at W-band. Int. J. Infrared Millim. Waves. vol. 17, no. 2., pp. 385–391. DOI: https://doi.org/10.1007/BF02088161 15. ARKHIPOV, A. V., BELOUS, O. I., BULGAKOV, B. M. and FISUN, A. I., 2002. Millimeterwave power combiner based on a half-open resonator. Int. J. Infrared Millim. Waves. vol. 23, no. 3, pp. 507–516. DOI: https://doi.org/10.1023/A:1015054124268 16. KUZMICHEV, I. K. and KHLOPOV, G. I., 1989. Matched excitation of the quasi-optical open resonators. In: Kvaziopticheskaya tekhnika mm i submm diapazonov. Kharkov, Ukraine: IRE AN USSR Publ. pp. 149–156 (in Russian). 17. VERTIY, A. A., DERKACH, V. N., POPENKO, N. A. and SHESTOPALOV, V. P., 1978. Experimental investigation of characteristics of the open resonators in the cylindrical cladding. Ukrainskii fizicheskii zhurnal. vol. 23, no. 10, pp. 1666–1672 (in Russian). 18. ANDROSOV, V. P. and KUZMICHEV, I. K., 1987. Influence on excitation efficiency of the open resonator of its parameters and connection with a waveguide. Kharkov, Ukraine: IRE AN UkSSR. Preprint no. 354 (in Russian). 19. KUZMICHEV, I. K., 2000. Matching of quasioptical open resonators with waveguide feeders. Radiophys. Quantum Electron. vol. 43, is. 4, pp. 294–302. DOI: https://doi.org/10.1007/BF02677194 20. VAINSHTEIN, L. A., 1988. Electromagnetic waves. Moscow, USSR: Radio i Svyaz' Publ. (in Russian). 21. KOGELNIK, H., 1964. Coupling and convertion coefficients for optical modes. In: Quasi-Optics. Symposium on Quasi-Optics Proceedings. Brooklyn, NY: Polytechnic Press, pp. 333–347. 22. BURSHTEIN, E. L., 1958. Power of non-planar waves received by an antenna. Radiotekhnika i Elektronika. vol. 3, no. 2, pp. 186–189 (in Russian). 23. KAY, A. F., 1960. Near-Field Gain of Aperture Antennas. IRE Trans. Antennas Propag. vol. 8, no. 6, pp. 586–593. DOI: https://doi.org/10.1109/TAP.1960.1144905 24. KUZMICHEV, I. K., 2009. Exitation efficiency of quasioptical resonance systems. Telecommun. Radio Eng. vol. 68, no. 1, pp. 49–63. DOI: https://doi.org/10.1615/TelecomRadEng.v68.i1.30 25. DELISIO, M. P. and YORK, R. A., 2002. Quasi-Optical and Spatial Power Combining. IEEE Trans. Microw. Theory Tech. vol. 50, no. 3, pp. 929–936. DOI: https://doi.org/10.1109/22.989975 26. VOLMAN, V. I. and PIMENOV, Y. V., 1971. Technical electrodynamics. Moscow, USSR: Svyaz' Publ. (in Russian). 27. SVELTO, O., 1990. Principles of lasers. Moscow, USSR: Mir Publ. (in Russian). 28. KUZMICHEV, I. K., 1991. Aperture excitation of the open resonators in the millimeter range: PhD. thesis ed. Rostov State University (in Russian). 29. SHESTOPALOV, V. P., KIRILENKO, A. A., MASALOV, S. A. and SIRENKO, Y. K., 1986. Resonance wave scattering. Vol. 1. Diffraction Gratings. Kyiv, Ukraine: Naukova Dumka Publ. (in Russian). 30. VAINSHTEIN, L. A., 1963. On the electrodynamic theory of gratings. Part 1. In: Elektronika bol'shikh moshchnostey. Moscow, USSR: USSR Academy of Sciences Publ. House. no. 2, pp. 26–56 (in Russian).